PRESERVING HERITAGE: ARCHITECTURAL RESTORATION AND DEVELOPMENT IN UZBEKISTAN'S HISTORIC TOWNS (Journal of Science-Innovative Research in Uzbekistan, 2023)
This scholarly article delves into the origins of Uzbekistan's ancient cities and their pivotal public centres, offering a historical narrative intertwined with themcontemporary challenges of restoration and development. It provides a detailednexploration of vanished historical city centres, focusing notably on the case study of the Fergana Valley. Through an insightful examination of the vanished centres' restoration and developmental issues, the article sheds light on the intricate complexities of preserving architectural heritage while adapting to modern demands. It presents a compelling narrative that navigates through the historical roots of Uzbekistan's urban hubs while concurrently addressing the restoration dilemmas faced in resurrecting these lost cultural landscapes. This exploration stands as a beacon, emphasizing the criticality of heritage preservation and adaptive architectural development, offering a pertinent and informative study for scholars, preservationists, and urban planners vested in the revival of Uzbekistan's historical urban tapestry